Anaesthesia provision challenges in public hospitals of Pakistan’s Punjab province: a qualitative study of expert perspectives - Natasha Howard; Rubeena Zakar; Sumbal Shahbaz (BMJ Open)
Objectives Anaesthesia delivery in Pakistan remains limited to conventional intraoperative procedures, with research showing ongoing challenges in quality and resourcing. We aimed to identify systemic challenges in the delivery of the WHO-World Federation of Societies of Anaesthesiologists’ (WHO-WFSA) ‘highly recommended’ standards of quality anaesthesia services for surgical support in Pakistan’s Punjab province.Study design and setting This single-method qualitative study included 22 semistructured interviews with purposively selected anaesthesia system experts in Punjab province, including heads of teaching hospital anaesthesia departments, healthcare commission (HCC) representatives and health department officials. We analysed data thematically, using deductive and inductive coding.Participants 10 participants worked as anaesthesia department heads of teaching hospitals across Punjab, 5 worked for the HCC and 7 worked for the health department. All were selected purposively and had at least 5 years of experience working as head of department or serving in legislative departments.Results We identified three themes experienced as major challenges within the specialty, namely anaesthetist recruitment and retention, quality of care and in-service training, and discrepancies between specialities. Findings indicated that workforce shortages and maldistribution, insufficient in-service training and standards, inadequate equipment maintenance and lack of anaesthesia representation in decision-making compromised anaesthesia provision quality and safety.Conclusions Improving anaesthesia provision in Punjab would require increasing physician and non-physician anaesthetist numbers and rotation to peripheral postings, strengthening training quality and ensuring availability of WFSA-specified essential equipment and supplies. To achieve essential anaesthesia provision standards, policy interventions are needed to, for example, balance anaesthesiologist and surgeon/obstetrician-gynaecologist numbers, require that anaesthesiology postgraduates work a few years in-country (eg, scholarship bonds), ensure in-service training attendance for skills updates and implement quality assurance standards for equipment and supplies.